Evaluation of chromatin accessibility in prefrontal cortex of individuals with schizophrenia - Bryois, Julien; Garrett, Melanie E.; Song, Lingyun; Safi, Alexias; Giusti-Rodriguez, Paola; Johnson, Graham D.; Shieh, Annie W.; Buil, Alfonso; Fullard, John F.; Roussos, Panos; Sklar, Pamela; Akbarian, Schahram; et al. (Nature communications, 2018)
Schizophrenia genome-wide association studies have identified >150 regions of the genome associated with disease risk, yet there is little evidence that coding mutations contribute to this disorder. To explore the mechanism of non-coding regulatory elements in schizophrenia, we performed ATAC-seq on adult prefrontal cortex brain samples from 135 individuals with schizophrenia and 137 controls, and identified 118,152 ATAC-seq peaks. These accessible chromatin regions in the brain are highly enriched for schizophrenia SNP heritability. Accessible chromatin regions that overlap evolutionarily conserved regions exhibit an even higher heritability enrichment, indicating that sequence conservation can further refine functional risk variants. We identify few differences in chromatin accessibility between cases and controls, in contrast to thousands of age-related differential accessible chromatin regions. Altogether, we characterize chromatin accessibility in the human prefrontal cortex, the effect of schizophrenia and age on chromatin accessibility, and provide evidence that our dataset will allow for fine mapping of risk variants. Chromatin accessibility may be altered in disease states. Here the authors carry out ATAC-seq on a large number of samples of dorsolateral prefrontal cortex from individuals with schizophrenia, and healthy controls.